Immunotherapy, Vascular Pathology, and Microhemorrhages in Transgenic Mice - Wilcock, Donna M.; Colton, Carol A. (CNS & Neurological Disorders - Drug Targets, 2009)
Alzheimer's disease (AD) is a progressive, neurodegenerative disorder that results in severe cognitive decline. Amyloid plaques are a principal pathology found in AD and are composed of aggregated amyloid- beta (Aβ) peptides. According to the amyloid hypothesis, Aβ peptides initiate the other pathologies characteristic for AD including cognitive deficits. Immunotherapy against Aβ is a potential therapeutic for the treatment of humans with AD. While anti-Aβ immunotherapy has been shown to reduce amyloid burden in both mouse models and in humans, immunotherapy also exacerbates vascular pathologies. Cerebral amyloid angiopathy (CAA), that is, the accumulation of amyloid in the cerebrovasculature, is increased with immunotherapy in humans with AD and in mouse models of amyloid deposition. CAA persists in the brains of clinical trial patients that show removal of parenchymal amyloid. Mouse model studies also show that immunotherapy results in multiple small bleeds in the brain, termed microhemorrhages. The neurovascular unit is a term used to describe the cerebrovasculature and its associated cells-astrocytes, neurons, pericytes and microglia. CAA affects brain perfusion and there is now evidence that the neurovascular unit is affected in AD when CAA is present. Understanding the type of damage to the neurovascular unit caused by CAA in AD and the underlying cause of microhemorrhage after immunotherapy is essential to the success of therapeutic vaccines as a treatment for AD.
Keywords: Immunotherapy